(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of the developed Caffarel model in developing the skills of infographic design in the subject of advertising art among students of the Institute of Fine Arts. The problem of the research lies in the fact that infographic designs represent an important source of financial returns for students after graduation, as they enable them to exploit their skills in making advertising designs. And commercial designs for companies. Accordingly, infographic designs can become a sustainable source of income and an opportunity for success in the labor market. While the importance of researching the developed Caffarell model is highlighted, it is one of the modern teaching models that falls under the umbrella of educational design. This model is characterized by interactivity, which puts the decision-making process in the hands of The responsible person, i.e. the teacher who plans educational programs that suit the needs of the learners. The researcher reached the following set of conclusions and recommendations: The impact of the Caffarel model developed for the benefit of the experimental group in teaching the subject of advertising art. It can be used as an effective means in learning and teaching to help the learner improve and develop skill performance. There is an impact of the developed Caffarel model for the benefit of the experimental group in developing infographic design skills in the subject of advertising art. Including topics and skills related to modern technologies that prepare students for the labor market and practicing them in the courses of the art of advertising. The impact of the developed Caffarel model on developing marketing skills for students of the Institute of Fine Arts in the subject of advertising art